2016
DOI: 10.1073/pnas.1522577113
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between oscillatory EEG activity and the laminar-specific BOLD signal

Abstract: Electrophysiological recordings in animals have indicated that visual cortex γ-band oscillatory activity is predominantly observed in superficial cortical layers, whereas α-and β-band activity is stronger in deep layers. These rhythms, as well as the different cortical layers, have also been closely related to feedforward and feedback streams of information. Recently, it has become possible to measure laminar activity in humans with high-resolution functional MRI (fMRI). In this study, we investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
169
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(188 citation statements)
references
References 74 publications
19
169
0
Order By: Relevance
“…The power effect in the current study was broadly limited to gamma band (24–150 Hz), and oscillations in this frequency range show a robust relationship with BOLD responses (Boorman et al, 2015; Hutchison et al, 2015; Scheeringa et al, 2016), rendering the two findings rather consistent. Interestingly, other fMRI studies on anxiety-like behavior in approach–avoidance conflict have also suggested an encoding of conflict per se and/or action tendencies in multivariate patterns of hippocampal BOLD signal (O'Neil et al, 2015; Loh et al, 2017).…”
Section: Discussionsupporting
confidence: 49%
“…The power effect in the current study was broadly limited to gamma band (24–150 Hz), and oscillations in this frequency range show a robust relationship with BOLD responses (Boorman et al, 2015; Hutchison et al, 2015; Scheeringa et al, 2016), rendering the two findings rather consistent. Interestingly, other fMRI studies on anxiety-like behavior in approach–avoidance conflict have also suggested an encoding of conflict per se and/or action tendencies in multivariate patterns of hippocampal BOLD signal (O'Neil et al, 2015; Loh et al, 2017).…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, studies using laminar fMRI have typically divided gray matter into several evenly spaced bins, as an approximation of the underlying cortical laminae ( Figure 1A and B). Consistent with the known functional architecture of the cortical column, these studies find feedback responses in deep and superficial, but not middle, cortical bins Kok et al, 2016;Muckli et al, 2015;Scheeringa et al, 2016). …”
Section: Forward Backward and Lateral Message-passing Within The Nesupporting
confidence: 71%
“…In this review, we have described some recent successful applications of laminar fMRI that characterized bottom-up and top-down responses in the contexts of visual prediction (Kok et al, 2016;Muckli et al, 2015) and selective attention Scheeringa et al, 2016). We have also outlined other areas of cognitive neuroscience research that stand to gain new insights from laminar fMRI, offering some specific hypotheses from the literature that yield testable predictions for laminar fMRI experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using variance in one type of response to guide analysis of another response provides a unique opportunity to bootstrap the spatial resolution of fMRI and temporal resolution of EEG. For example, Scheering, Koopmans, Van Mourik, Jensen, and Norris (2016) use combined EEG/fMRI to show the laminar specific origin of oscillatory EEG responses (e.g. that gamma-band EEG is linked to BOLD responses in superficial cortical lamina); thereby replicating in human cortex observations that could previously only have been obtained from invasive methods.…”
Section: Future Directionsmentioning
confidence: 99%